Phenotyping of outpatients with heart failure with preserved ejection fraction and poor prognosis - V. N. Larina; V. I. Lunev (Российский кардиологический журнал, 2024)
The applicability of the left ventricular global function index (LVGFI) and its derivative, determined by echocardiography, to distinguish clinical phenotypes in a cohort of patients with heart failure with preserved ejection fraction (HFpEF) is unknown.Aim. To evaluate the differential diagnostic potential of LVGFI and its derivative when phenotyping outpatients aged ≥60 years with HFpEF.Material and methods. A total of 140 outpatients (men, 43%) aged 73 (67-78) years with functional class II-IV HFpEF were included in the study. The follow-up period was 34 (22-36) months.Results. LVGFI was 22,4 (19,4-24,6)%, while derivative index of LVGFI — 283,9 (248,9-332,2) ml. There were 18 (12,9%) deaths. The threshold value for predicting death for LVGFI was ≤21,4%, for derivative index of LVGFI — ≥303,6 ml. Based on cluster membership and mortality analysis, two following risk groups for death of patients with HFpEF were identified: a relatively low-risk (group 1) and moderate (group 2) risk group (mortality within 34 months ~25%). Group 1 was represented by patients, predominantly male, with class II HFpEF, coronary artery disease (CAD) and prior myocardial infarction (MI), concentric hypertrophy, a significant LV mass increase, a high frequency of bendopnea, lower LVGFI and higher derivative index of LVGFI. Group 2 was represented by patients, predominantly female, with class II HF, a history of CAD and myocardial infarction, concentric hypertrophy and concentric remodeling, a moderate LV mass increase, a relatively low frequency of bendopnea, higher LVGFI and lower derivative index of LVGFI. Based on the data obtained, an algorithm was developed to determine the risk of death in patients with HFpEF.Conclusion. LVGFI and its derivative index can be used in phenotyping patients with HFpEF. The developed algorithm for determining the death risk makes it possible to identify outpatients with HFpEF who need intensified therapy and observation by a general practitioner and cardiologist in order to reduce the risk of an unfavorable prognosis.